Determinants of burnout in project management context, introducing the concept of "Project burnout" - Selamoğlu, Atakan (Graduate School, 2023)
Burnout is a trending subject in the post-pandemic business space, while project management corresponds to an important ratio of global economic activities and active work-force. However, the cross section of these two fields of study have been neglected so far and current literature shows that burnout studies within the context of project environment were limited and thus understudied. Based on this gap identified in the literature, a study is planned to investigate the drivers of burnout within the context of project management. Burnout is defined as a long-consequence of mental strain and a fundamental crisis in the psychological connections that people establish with work. In addition, World Health Organization identifies burnout as an occupational phenomenon and a state of vital exhaustion. Burnout is comprised of three main dimensions; exhuastion, cynicism and professioanl inefficacy and is triggered by several drivers, with six main dimensions identified in burnout literature; work overload, lack of control, insufficient reward, breakdown of community, absence of fairness and conflicting values. Finally, there are several alternative scales to measure burnout, Maslach Burnout Inventory being one of the most widely accepted and applied approach which is also used in our research. On the other hand, project management is an established industry receiving attention from both academic and business environments. Projects are temporary endeavors to create value through unique products, services and processes, while project management is the application of skills, tools and techniques to project activities to meet project requirements. Projects are basically defined with iron triangle concept, with cost, time and quality limitations on the vertices. However, this simplified approach is not sufficient to understand the complex and complicated nature of projects. Project complexity network is identified as a useful lens to understand the nature of projects and identify the parameters that may eventually lead to burnout. Project complexity field is dominated by two main lines of thinking, one of which is system complexity and the other is perceived complexity. The synthesis of both approaches yield a comprehensive and thorough view of the project complexity parameters, which can be linked to burnout drivers. This approach is used to create a section of the questionnaire to understand and evlaute how complexity defining parameters are linked to burnout dimensions. As discussed, projects have unique features defined by deadlines, tight budgets, quality expectations and complex stakeholder relations. It is an exhausting and demanding environment for project management professionals, which is an obvious setting for burnout experience. We are dealing with a unique and sovereign setting, which has also been neglected so far. Therefore, suggesting a definition for "project burnout" is accepted as a good starting point and a novel step for raising attention and eventually creating a legitimate field of interest. Project burnout is defined as a fundamental crisis in the psychological connections of any individual with the work, resulting from long-term consequence of mental strain caused by project-related parameters and imbalance between project demands and project resource. Following the literature review and proposition of a definition for project burnout, a cross-sectional survey study is applied to investigate the link between parameters derived from project complexity and burnout dimensions. The context of research is Turkish defense industry. It should be noted that defense industry can be labelled as a tailor-made opportunity to investagate project burnout. Defense industry projects have high level of technological development, large budgets, long and strict lead times and tightly regulated control processes run by customers. It is a sophisticated work environment and professionals working in defense projects are considered be elite in their skills and experiences. The audience has a good level of awareness, skills and expertise regarding project management as well. The questionnaire consists of two main scales for burnout and project parameters. 126 fully completed responses are received, except the company information and names of the individuals. Almost a 10% return rate is achieved, which is acceptale considering the dominant privacy driven culture in the industry. 8 hypotheses are suggested, defining the expectation about direct and moderating relationships among project complexity parameters grouped under levels of interested subjects (project parameters, individual parameters, team parameters and organization parameters) and burnout dimensions (exhaustion, cynicism and personal inefficacy). Exploratory factor analysis and confirmatory factor analysis are applied to figure out the structure defining factors and latent variables. Then, path analysis is applied by SmartPLS 4, a software utilizing structural equation modelling. The findings indicated that "project size and dependencies", "individual experience and role", "team fitness and autnomy", "team diversity and competence" and "organization competence and environment" are identified as primary factors or latent variables in our context. The inner model also partially supported 4 of the hypotheses, while rejecting remaining 4. There are no significant moderating impacts of individual, team and organization parameters on each other's relationship to any burnout dimensions. In addition, project size and dependencies only have moderating role, while lacking a significant direct relationship with any of the burnout dimensions. The limitations, proposed future research directions and practical implications are discussed. Briefly, any contributing study is highly anticipated to increase the legitimacy of the project burnout concept, validate the presented findings in a variety of project settings and increase awareness of organizations about burnout phenomenon and its damaging outcomes. It is crucial in times when human resource is considered as the main asset of any organization and in an era where mental wellbeing of individuals are at stake.
Proje yönetim bağlamında tükenmişliğin nedenleri, "Proje tükenmişliği" kavramının tanıtımı
Thesis (Ph.D.) -- Istanbul Technical University, Graduate School, 2023
Keywords: project management; proje yönetimi; burnout; tükenmişlik